Voltaic Cell Learning Design Using the RADEC (Read, Answer, Discuss, Explain, and Create) Model Oriented toward the Pancasila Student Profile - Nursida Sutantri; Wahyu Sopandi; Wawan Wahyu; Abdul Latip (Chemistry Education Department, 2023)
This study aimed to describe the Voltaic Cell learning design using the RADEC (Read, Answer, Discuss, Explain, and Create) learning model based on the Pancasila Student Profile. The approach employed in this research was descriptive qualitative. The research instrument was a validation sheet in the form of a questionnaire administered to five validators, consisting of two Expert Lecturers in Chemistry Education at Universitas Pendidikan Indonesia and three Chemistry teachers who taught at Sekolah Penggerak in Bandung City, employing the Merdeka Curriculum. The data processing results demonstrated an average percentage of 96.7% for the alignment of the lesson plan across four aspects: Formulation of Competency Achievement Indicators and Learning Objectives, Presented Content, Language Usage, and Time Allocation. The findings also indicated a connection between the voltaic cell learning activities using the RADEC learning model and the manifestation of the Pancasila Student Profiles, including Faith in God Almighty, Noble Characters, Global Diversity, Mutual Cooperation, Independence, Critical Reasoning, and Creativity, producing an average percentage of 95.4% classified into the excellent category. Hence, this study signified that the voltaic cell learning design using the RADEC model could cultivate the Pancasila Student Profile.